2021
DOI: 10.1073/pnas.2104420118
|View full text |Cite
|
Sign up to set email alerts
|

Benzofuran sulfonates and small self-lipid antigens activate type II NKT cells via CD1d

Abstract: Significance Whereas T cells are known to recognize peptides, vitamin B metabolites, or lipid antigens, we identify several nonlipidic small molecules classified as pentamethylbenzofuransulfonates (PBFs) that activate a population of CD1d-restricted natural killer T (NKT) cells. This represents a breakthrough in the field of NKT cell biology. This study also reveals a previously unknown population of PBF-reactive NKT cells in healthy individuals with stereotyped receptors that paves the way for futur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 60 publications
2
12
0
Order By: Relevance
“…Moreover, two of the TCR alpha clonotypes therein described fit the CAIT CDR3 motif (figure 1B). 19 36 Given these results, we hypothesise that CAIT cells may be reactive to CD1d and thus be a semi-invariant subgroup of the NKT type II family. Indeed, identification of HLA and antigen specificity is an essential step in T cell characterisation.…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, two of the TCR alpha clonotypes therein described fit the CAIT CDR3 motif (figure 1B). 19 36 Given these results, we hypothesise that CAIT cells may be reactive to CD1d and thus be a semi-invariant subgroup of the NKT type II family. Indeed, identification of HLA and antigen specificity is an essential step in T cell characterisation.…”
Section: Discussionmentioning
confidence: 89%
“…Recent experimental evidence has demonstrated that NKT cells are capable of recognizing drug-like small molecules that are presented through a CD1d restricted pathway. 33 The role of nonconventional T-cells will be further discussed in following sections.…”
Section: Stevens-johnson Syndrome and Toxic Epidermalmentioning
confidence: 99%
“…133 Further studies using PPBF analogues resembling sulfonamides were evaluated but these studies failed to show activation of the ABd TCR (type II NKT cell clone) and the NKT15 TCR (type I NKT cell clone). 33 However, it is possible that other clones of the type I or II have a better affinity toward these compounds. Interestingly, when the halogenated derivative of PPBF was loaded with a CD1d tetramer, αβ T-cells and γδ Tcells were detected.…”
Section: Brief Description Of Nonconventional T-cells Discovered In 1...mentioning
confidence: 99%
See 2 more Smart Citations